2018
DOI: 10.14202/vetworld.2018.1706-1711
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes of immediate skin expansion of the distal limb of rats

Abstract: Aim:Tissue expansion is an applicable technique to reconstruct many surgical defects. The aim of this research was to evaluate the histological changes caused by immediate skin tissue expansion in rats as an animal model.Materials and Methods:Immediate skin tissue expansion in 18 adult female rats was performed using three different sizes (small, medium, and big) of polymethylmethacrylate tissue expanders at the dorsal surface of the metatarsal area of the right limb. The contralateral limb was served as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Histological changes of tissue expansion in the mouse model indicated a significant increase in epidermal thickness and a decrease in the dermal layer after expansion from 2 weeks to 5 weeks. 7,8 Pasyk et al 9 reported similar results in histological changes in humans and reported subcutaneous tissue thinned significantly after expansion. The increase in mitosis and turnover of keratinocytes in the basal cell layer of the epidermis may explain the increase in epidermal thickness.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Histological changes of tissue expansion in the mouse model indicated a significant increase in epidermal thickness and a decrease in the dermal layer after expansion from 2 weeks to 5 weeks. 7,8 Pasyk et al 9 reported similar results in histological changes in humans and reported subcutaneous tissue thinned significantly after expansion. The increase in mitosis and turnover of keratinocytes in the basal cell layer of the epidermis may explain the increase in epidermal thickness.…”
Section: Discussionmentioning
confidence: 74%
“…The inclusion criteria were all as follows: (1) no less than 18 years old and (2) body mass index (BMI) in the normal range (18. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The exclusion criteria were any of the following: (1) history of previous surgery or injury in the forehead area; (2) cranial deformity; (3) dermatosis; (4) insufficiency of documentation regarding measurements by ultrasound device or postoperative follow-up; (5) a long history of smoking or drinking; (6) chronic diseases including cardiovascular diseases, metabolic diseases, and immune diseases; and (7) complications during expansion including infection, expander exposure, or expander rupture.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Raymond et al 11 reported that the anterolateral thigh flaps shrunk by 25% after harvesting on average in clinical practice, and the reduction in flap size correlated with flap width and thickness. Histologic changes in tissue expansion indicated a significant increase in epidermal thickness and a decrease in the dermal layer after expansion 12,13 . The microstructure of the tissue also changes after tissue expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Histologic changes in tissue expansion indicated a significant increase in epidermal thickness and a decrease in the dermal layer after expansion. 12,13 The microstructure of the tissue also changes after tissue expansion. After expansion, most of the fibroblasts transform into myofibroblasts, which typically express α-SMA protein and become the driving force of fibrotic tissue contracture.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms of mechanical stretch‐induced skin regeneration during expansion are not clear 1 . Previous studies have shown that cell proliferation in response to the mechanical forces of expansion leads to an increase in cell numbers, while increased synthesis of extracellular matrix is the main source of post‐expansion skin regeneration, which is attributed to the response and complex regulation of mechanical stimuli at the molecular and cellular levels 2,3 . Mechanical forces affect ion channels in cell membranes and intracellular second messengers, causing changes in complex signalling pathways and inducing the expression of various cytokines, which in turn cause proliferation of epidermal and dermal cells, collagen synthesis and degradation, and lead to an increase in total collagen and skin neovascularization 4,5 …”
Section: Introductionmentioning
confidence: 99%